The Efficiency of Certain Amino Acids in Regulating chABCI Gene Expression in Proteus mirabilis - Ibrahim, Ghena Jameel; Laftaah, Bahaa Abdullah (Iraqi Journal of Science, 2024)
Many previous studies have demonstrated the therapeutic importance of chondroitinase ABC encoded by the chABCI gene. This study, however, accomplished to determine some amino acids effects on the chABCI gene in Proteus mirabilis to regulate chondroitinase production. A total of 57 (96.61%) isolates of Proteus mirabilis and two (3.39%) isolates of Proteus vulgaris were obtained from clinical specimens. The impact of amino acids on bacterial growth was assessed by gauging the turbidity of the nutrient broth using a spectrophotometer. Two isolates of P. mirabilis were treated with amino acids and their effect on the gene expression of the chABCI gene was studied using a real-time polymerase chain reaction. L-tyrosine and L-serine significantly increased bacterial inhibition (p < 0.05), while L-arginine, L-glutamine, L-proline, L-cysteine and glycine didn’t significantly affect P. mirabilis growth (p > 0.05). Also, gene expression increased significantly (p < 0.05) for chABCI with varying degrees when treated with these amino acids in addition to L-serine. Whereas L-tyrosine had a significant effect in reducing gene expression (p < 0.0001). It can, therefore, be concluded that amino acids significantly affect the gene expression of chABCI, either by increasing or inhibiting it.